The Granger Causality on Economic Growth and Government Expenditure in Asean - Farhan Rizqullah Azhari; Putri Bintusy Syathi; Miksalmina; Megawati (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
The expansion of the economy and public expenditure are central issues in a country's macroeconomic analysis, which is generally analyzed through two main approaches, namely the Keynesian and Wagnerian perspectives. The purpose of this study is to explore the cause-and-effect relationship between economic growth and government spending in selected ASEAN countries, namely Indonesia, Malaysia, Singapore, and Thailand, throughout the 1974–2023 timeframe. The Granger causality method was applied to perform the analysis. The results indicate that only in Singapore is there a one-way causal relationship from economic growth to government spending. This means that increased economic growth drives an increase in public spending. This finding supports the applicability of Wagner's law in Singapore, where growing economic activity is followed by increased government fiscal intervention in the form of public service provision. Conversely, in Indonesia, Malaysia, and Thailand, no significant causal relationship was found, either one-way or two-way. This indicates that neither the Keynesian nor Wagnerian views have been empirically proven in these three countries during the observation period. In these countries, economic growth has not directly driven an increase in government spending, and conversely, government spending has not been proven to drive economic growth. Therefore, in terms of policy, Singapore needs to continue to maintain and enhance its economic growth in order to expand the provision of public facilities.